Integrating Comprehensive Rehabilitation Care to Multimorbidity Approach: A Challenge for the Chilean Public Health System - Paula Zamorano; Fernanda Calvo; Ricardo Banda; Javiera Fuentes; Clara Molina; Elena Medina; Marcela Gonzalez-Madrid (International Journal of Integrated Care, 2024)
The multimorbidity approach involves promotional and preventive strategies. The demand for rehabilitation services has grown exponentially in recent years, leading to the urgency of rethinking care delivery. In Chile, there are laws, programs, and guidelines that, from their theoretical basis, include a person-centered care focus. But in real practice, multiple barriers trigger important fragmentation of care. In response, a new strategy has been proposed to answer whether comprehensive rehabilitation care based on multimorbidity positively impacts the health system performance, people’s functionality, and quality of life, which will be implemented as a pilot study with a national scale-up focus. Resumen El enfoque de multimorbilidad implica estrategias promocionales y preventivas. La demanda de servicios de rehabilitación ha crecido exponencialmente en los últimos años, lo que ha llevado a la urgencia de repensar la organización y entrega de prestaciones. En Chile existen leyes, programas y lineamientos que, desde su base teórica, incluyen un enfoque de atención centrado en la persona. Pero en la práctica real, múltiples barreras generan una importante fragmentación de la atención. En respuesta, se ha propuesto una nueva estrategia para responder si una rehabilitación integral basada en el enfoque de la multimorbilidad impacta positivamente en el desempeño del sistema de salud, la funcionalidad de las personas y la calidad de vida, que se implementará como un estudio piloto con un enfoque de escalamiento nacional. Palabras clave: Cuidado centrado en la persona; rehabilitación; multimorbilidad; interdisciplina